Antiracist Academic Leadership: Confronting Whiteness - David S Owen (Academic Chairpersons Conference Proceedings, 2020)
What obligations do academic leaders have to address the ways whiteness impacts departmental and campus climates? And what are some strategies chairpersons can take to mitigate the ways whiteness creates inequitable conditions for students, faculty, and staff success? Participants in this session will have an opportunity to discuss these and other questions and explore the requirements of academic leadership that is avowedly antiracist.
Keywords: leadership; whiteness; privilege; oppression; racism